Seamless vertical handover between 3g universal mobile telecommunications system and wireless LAN with modified mobile stream control transmission protocol - Hamza, Bashar Jabbar (2011)
With an increasing popularity in different kinds of wireless technologies, an internet user can acquire universal wireless access with a mobile node (MN). Different wireless technologies can make up a heterogeneous wireless network (HWN) such as universal mobile telecommunications system (UMTS) and wireless local area networks (WLAN). Communications between two or more different access networks will undergo vertical handover (VHO). To achieve the seamless VHO and smooth mobility in the HWN between UMTS and WLAN, a mobile stream control transmission protocol (mSCTP) is exploited in this thesis. A MN may experience performance degradation during VHO due to the deficiencies of mSCTP such as selective acknowledgement (SACK) transmission lost, packet retransmission timeout and packet reordering. These deficiencies occur due to the disparty of given bandwidth and propagation delay between UMTS and WLAN access paths. In order to overcome these deficiencies, a packet reordering model (PRM) is proposed. The proposed PRM works as a special buffer with a large capacity to receive all transmission sequence numbers (TSNs). It then forwards all incoming abovementioned data chunks to the MN/WLAN or MN/UMTS networks after the VHO. The performance of the scheme is simulated and analyzed using NS-2 simulator. The simulation results show that the proposed PRM scheme enhances the performance throughput by 16% compared to conventional mSCTP. Also, the congestion window (CWND) of the mSCTP will be increased during VHO by 21 % when the proposed scheme is exploited.In addition, we also propose a new scheme which is a hybrid scheme of mSCTP with bicasting mechanism called Bi-mSCTP under the mobile internet protocol (MIP) to overcome the MIP issues such as hybrid routing, registration delay, data session disruption during VHO, and packet overhead. These issues occur when the data packets of the MIP are sent from a foreign agent (FA) to a home agent (HA) via a tunnel when a MN moves to a new network. When a MN is in the area of VHO the proposed scheme relies on the generated mSCTP signals to allocate a new care-ofaddress (CoA) to the corresponding node (CN) dynamically before the link layer handover. At the same time, it inserts a bicasting flag inside the address configuration (ASCONF) control chunk to inform the CN to start the transmission over both WLAN and UMTS links. The system performance was analyzed using the NS-2 simulation tool. The results showed that the hybrid Bi-mSCTP scheme introduces approximately 1.02s and 2.64s reduction in delay performance over both mSCTP and MIP schemes respectively. It also reduces the packet loss rate by more than 21.7% and 45% compared to mSCTP and MIP, respectively Finally, we proposed SHP scheme, a Seamless VHO Scheme, which is a combination of the hybrid Bi-mSCTP and PRM schemes. SHP scheme adopts the advantage of hybrid Bi-mSCTP and PRM schemes to achieve better serve for fastmoving users and smooth mobility in the HWN between cellular UMTS and WLAN networks. The simulation results showed that the proposed SHP scheme outperforms the other three schemes (conventional mSCTP, MIP and SIGMA schemes) in terms of VHO delay, throughput, and packet loss. In addition, the simulation results confirm that the proposed SHP scheme can achieve a smooth VHO and keep the VHO delay a minimum.